Hubungan Usia, Pendidikan, Pekerjaan, dan Keterpaparan Informasi Terhadap Pengetahuan, Sikap, dan Tindakan Pola Asuh Anak Stunting pada Ibu Peserta Program KPG di Puskesmas Grogol Selatan - Fitriani, Evita Nur; Harjatmo, Titus Priyo; Wiyono, Sugeng; Marbun, Rosmida Magdalena (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Stunting is a disorder that occurs in a child's nutritional status, where the child's height is relatively short compared to his age. Based on the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunted toddlers in South Jakarta is 11.9%. The incidence of stunting is still a concern that must be addressed immediately. South Grogol Community Health Center created a program, namely KPG. The aim of this research is to determine the relationship between age, education, employment and exposure to information on the knowledge, attitudes and actions of mothers participating in the KPG program at the South Grogol Community Health Center. This type of research was carried out, namely analytical observational with a cross sectional design. Samples were taken by total sampling. The research results showed that 58.8% were aged 36 – 45 years, 76.5% had higher education, 82.3% had nonworking/domestic status, the level of exposure to good information was 64.7%. The level of knowledge in the good category is 76.5%, attitude in the positive category is 70.6%, and action in the poor category is 58.8%. Obtained significant results on knowledge based on education level with a p - value of 0.022 and significant results on attitudes based on exposure to information with a p - value of 0.028. For health workers, the KPG program can remind respondents to apply the knowledge gained from the KPG program to their daily parenting patterns. This is done to maintain and improve children's nutritional status in a good direction.Keywords : Characteristic, Exposure to Information, Knowledge, Attitudes, Actions